Investigation of Workers' Food and Suggestions as to Dietary - Hill, Leonard, Sir, 1866- (London : His Majesty's Stationery Office)
1917-10 1917 1910s 12 pages 8 The results obtained by these two schemes, which closely agree, are set out in the following Tables III and IV TABLE III. HOSTEL DAILY DIETARY PER MAN. (Calculated from data supplied by Management.) Meal. Ingredients. Weight in grammes. Gross. When dried. Protein. Fat. Carbohydrate. Breakfast 3½ oz. Bacon 110 25.3 47.0 — ½ „ Butter 14 0.3 11.3 — 6 „ Bread 170 12.0 2.0 89.4 1 „ Sugar 28 — — 28 1/6 pint Milk 80 c.c. 2.5 3.0 4 1 oz. Jam 28 — — 14 Dinner ...... 7 oz. Fish 200 36.2 1.0 — 8 „ Potatoes 228 4.0 — 55 3 „ Bread 85 6.0 1.0 44.7 8 „ Pudding 228 7.3 9.3 70 Tea......... 1 oz. Sugar 28 — — 28 1 „ Butter 28 0.6 22.6 — 4 „ Bread 114 8.0 1.4 60 1/6 pint Milk 80 c.c. 2.5 3.0 4 Supper ...... 4 oz. Meat 114 37.6 3.5 — 1 „ Butter 28 0.6 22.6 — 1½ „ Pickles 43 — — 5 6 „ Bread 170 12.0 2.0 89.4 All meals ...... — — — 154.9 129.7 491.5 Calorie value:— Total 3,856 635 1206 2015 The food consumed by women similarly worked out gives a total of 3,070 calories. TABLE IV. HOSTEL AVERAGE DIETARY PER MAN. (Data obtained by personal visit.) Meals. Ingredients. Dry weight in Grammes. Calories. Protein. Fat. Carbohydrate. Breakfast Sausage 6.3 8.2 12.2 1020.9 Bacon 15.1 30.5 — Bread 12.1 8.4 96.7 Dinner Meat 42.7 4.0 — 973.8 Potatoes 3.7 — 50.6 Cabbage 2.5 — 9.5 Apple pie 5.3 21.2 66.3 Tea Bread, butter and jam 13.8 9.6 111.6 603.4 Supper Bread, butter, ham and cheese 44.6 55.8 96.0 1097.4 127/NU/5/5/1/1